Fenologia de cinco espécies herbáceas em duas áreas(preservada e antropizada) de uma floresta tropical seca (caatinga) - SOUZA, Diego Nathan do Nascimento (2012)
Plants may present a broad variation in phenological features, as a consequence of the interaction between biotic and abiotic factors that influence reproductive success. Thus, areas that are subjected to different degrees of anthropogenic pressure offer distinct conditions to the establishment and development of plant populations, including the occurrence and the intensity of phenological events. One of the most important factors that influence plant development in dry forests is the precipitation, mainly for annual herbaceous species, which generally grow and reproduce in the rainy season. The phenology of these plants is poorly documented, mainly in the caatinga, a dry forest vegetation that grows in NE Brazil. For this reason, this study aims to learn more about the phenology of caatinga grass, with the following hypotheses: 1. The period of manifestation of phenophases may differ between a disturbed and a preserved area in a region of caatinga. 2. The level of synchrony of the populations of phenophases occur simultaneously in both areas tend to be different. 3. The amount of flowers and fruits of herbaceous populations studied may be different among sites (preserved and anthropic). 4. The manifestation of phenophases of herbaceous annual can have a correlation with local rainfall during its life cycle. The study was conducted in two areas of caatinga vegetation. One of them is a remnant of caatinga forest, hereafter called preserved one, and the other is an area that is regenerating, when occurred the abandone of agricultural practices. Bothe areas are located in the Instituto Agronômico de Pernambuco, Caruaru municipality, NE Brazil. In each area the vegetative and reproductive phenophases of 30 individuals of five annual, herbaceous species: Bidens bipinnata L., Commelina obliqua Vahl, Delilia biflora (L.) Kuntze, Desmodium glabrum (Mill.) DC. and Pseudabutilon spicatum (Kunth) R.E. Fr., were accompanied weekly during all their life cycle, understood from January to October 2011. The period, synchrony, number of reproductive structures and levels of correlation between precipitation and phenophases were compared between the two areas. It was observed a high synchrony in the phenological events between the two areas. It was found that the populations did not show strong variations in time and timing of their phenophases between the two environments. However, only one species did not show a high synchronization in flowering, fruiting and leaf drop for both areas. It was also noted that four species showed significant differences in number of reproductive structures produced by each population, demonstrating the interference of phenological areas in this regard. On the other hand, while it is true that many plants of the caatinga have a dependence on rainfall for its development was not seen any significant correlation between this factor and reproductive phenophases of herbs in two areas during their life cycle. For vegetative phenophases were observed a significant correlation with the local precipitation. Finally, the results of this study indicate that there is not a noticeable difference in the manifestation of phenophases in populations of the savanna grasses therophytes present in the immediate environment, but subject to different conditions as to shift the time of the phenophase, or in sync. However, the productivity, abandoned cultivation area had a greater production of reproductive structures of populations of Bidens bipinnata and Commelina obliqua, while the preserved area was more favorable for a higher production of reproductive structures of populations and Pseudabutilon spicatum and Desmodium glabrum. Thus, some herbaceous species have a more positive relationship with regenerating areas, favoring their phenological responses, while others do not have this type of relationship with these areas.